Improving the safety of cell therapy products by suicide gene transfer - Jones, Benjamin S.; Lamb, Lawrence S.; Goldman, Frederick; Di Stasi, Antonio (Frontiers in Pharmacology, 2014)
Adoptive T-cell therapy can involve donor lymphocyte infusion (DLI) after allogeneic hematopoietic stem cell transplantation, the administration of tumor infiltrating lymphocyte (TILs) expanded ex-vivo, or more recently the use of T cell receptor (TCR) or chimeric antigen receptor (CAR) redirected T cells. However cellular therapies can pose significant risks, including graft-versus-host-disease and other on and off-target effects, and therefore strategies need to be implemented to permanently reverse any sign of toxicity. A suicide gene is a genetically encoded molecule that allows selective destruction of adoptively transferred cells. Suicide gene addition to cellular therapeutic products can lead to selective ablation of gene-modified cells, preventing collateral damage to contiguous cells and/or tissues. The ‘ideal’ suicide gene would ensure the safety of gene modified cellular applications by granting irreversible elimination of ‘all’ and ‘only’ the cells responsible for the unwanted toxicity. This review presents the suicide gene safety systems reported to date, with a focus on the state-of-the-art and potential applications regarding two of the most extensively validated suicide genes, including the clinical setting: herpes-simplex-thymidine-kinase (HSV-TK) and inducible-caspase-9 (iCasp9).